2013
DOI: 10.1179/1476830513y.0000000063
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic expression of anorexigenic and orexigenic hormone receptors in obese femalesNeotomodon alstoni:Effect of fasting

Abstract: Obesity is a world problem that requires a better understanding of its physiological and genetic basis, as well as the mechanisms by which the hypothalamus controls feeding behavior. The volcano mouse Neotomodon alstoni develops obesity in captivity when fed with regular chow diet, providing a novel model for the study of obesity. Females develop obesity more often than males; therefore, in this study, we analysed in females, in proestrous lean and obese, the differences in hypothalamus expression of receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(41 reference statements)
2
3
0
Order By: Relevance
“…Cells expressing c-Fos photoinduction in SCN were observed at both CT 14 and CT 22; a larger difference in some cells expressing c-Fos was noted in obese mice at CT 22 (Figure 3B). We previously found that photic phase shifts were shorter at CT 14 in obese mice ([42]; and the present work). However, we did not find an equivalent directional change in the photic induction at CT 14.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Cells expressing c-Fos photoinduction in SCN were observed at both CT 14 and CT 22; a larger difference in some cells expressing c-Fos was noted in obese mice at CT 22 (Figure 3B). We previously found that photic phase shifts were shorter at CT 14 in obese mice ([42]; and the present work). However, we did not find an equivalent directional change in the photic induction at CT 14.…”
Section: Discussionsupporting
confidence: 74%
“…The possibility that a differential expression of VPAC2 receptors occurs in the SCN of obese Neotomodon should be tested. In a previous study, we observed differences in VPAC2 expression [42] as well as more unstable phase angle with the zeitgeber in obese Neotomodon [40]. In the present study, a larger dispersion of the free-running period was observed in obese animals, compared with a lengthening in period observed in obese mice fed with high-lipid diets [29].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Adult male Mexican volcano mice ( N alstoni , n = 5) were bred and raised in the animal facility of the Facultad de Ciencias, Universidad Nacional Autónoma de México, individually housed in a light‐ and temperature‐controlled environment (12 hr light/dark cycle, 23°C), and with free access to chow and water. Once animals reached 6 months of age, individuals identified as nonspontaneous obese (Báez‐Ruiz et al, ; Carmona‐Alcocer et al, ) were used in the remaining of the experiment. All handling of N alstoni animals followed the ethical guidelines of the National Research Council of the National Academy of Sciences Guide for the Care and Use of Laboratory Animals and the Official Mexican Standard NOM‐062‐Z00‐1999.…”
Section: Methodsmentioning
confidence: 99%